Requirements and Recommendations for an Enhanced Meeting Vewing Experience - Junuzovic, Sasa; Hegde, Rajesh; Zhang, Zhengyou; Chou, Phil A.; Liu, Zicheng; Zhang, Cha (Multimedia 2008, 2008)
We have found that viewing recorded meetings using traditional meeting viewers whose interfaces consist of an automatic speaker and a fixed context view does not provide sufficient information and control to the users. In particular, a survey of users who watch meeting recordings on a regular basis revealed that it is also useful to provide (1) speaker-related information, including who the speaker is talking to, looking at, and being interrupted by, and (2) more control of the interface, including changing the relative sizes of the speaker and context views and navigating within the context view. We present a 3D interface prototype designed specifically to meet these requirements when viewing recorded meetings. We describe in detail the results of a user study comparing the effectiveness of the new and traditional style interfaces with respect to these requirements. Based on this study, we present a set of guidelines for future interfaces.